Global Comprehensive Literature Review and Meta-Analysis of Brucella spp. in Swine Based on Publications From 2000 to 2020 - Gong, Qing-Long; Sun, Yu-Han; Yang, Yang; Zhao, Bo; Wang, Qi; Li, Jian-Ming; Ge, Gui-Yang; Chen, Zi-Yang; Shi, Kun; Leng, Xue; Zong, Ying; Du, Rui (Frontiers in Veterinary Science, 2021)
Background: Brucellosis, a zoonotic disease, infects various hosts, including swine and humans. It has reemerged in recent years as a public health concern, and current studies on brucellosis infection in swine have been conducted worldwide. However, no meta-analyses of global brucellosis infection in swine have been published. The aim of this study was to provide an overview of Brucella species (spp.) in swine worldwide and the factors associated with its persistence. Results: We searched seven databases for published epidemiological studies on brucellosis in pigs, including the Chinese National Knowledge Infrastructure, Wanfang Data, SpringerLink, ScienceDirect, Web of Science, the VIP Chinese Journal Database and PubMed. We selected 119 articles published from January 1, 2000 to January 3, 2020 for inclusion in the meta-analysis and analyzed the data using a random-effects model. Funnel plots and Egger’s test showed significant publication bias in the included studies. The results of the sensitivity analysis showed that our study was relatively stable and reliable. The prevalence of brucellosis in swine was 2.1% (95% CI: 1.6-2.6), of which the highest infection rate, which was found in Europe, was 17.4% (95% CI: 11.1-24.9). The prevalence in feral pigs (15.0%, 95% CI: 8.4-23.2) was higher than that in domestic pigs (1.1%, 95% CI 0.2-2.5). The prevalence in high-income countries (15.7%, 95% CI 8.0-25.3) was significantly higher than that in middle- (0.8%, 95% CI 0.5-1.1), and low-income countries (0.1%, 95% CI 0.0-0.2). The prevalence was highest in finishing pigs at 4.9% (95% CI 0.9-11.0), and lowest among suckling pigs at 0% (95% CI 0.0-0.5). Conclusion: The Brucella prevalence in pig herds currently is distributed widely throughout the world. In some countries, swine brucellosis may be a neglected zoonotic disease. We recommend long-term monitoring of the prevalence of brucellosis in domestic and wild pig herds. Attention should also be paid to animal welfare on intensive pig farms; controlling the breeding density may play an important role in reducing the spread of brucellosis among pigs.